PENGARUH TANGGUNGJAWAB ORANGTUA TERHADAP PERTUMBUHAN ROHANI KAUM REMAJA USIA 13-16 TAHUN DI DESA LUMBAN LOBU KECAMTAN BONATUA LUNASI KABUPATEN TOBA SAMOSIR TAHUN 2017 - Mory Nugraha Nainggolan (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2018)
Abstract, This study aim to know the influence of parental responsibility on the spiritual growth of teenagers aged 13-16 years in the Desa Lumban Lobu Kecamatan Bonatua Lunasi Kabupaten Toba Samosir 2017. The hypothesis of this study is that there is a positive and significant between parental responsibility on the spiritual growth of adolescents. This research is descriptive quantitative research. The population of this study amounted to 150 people with the number of research samples as many as 45 people namely 30 % of the population. The instrument used in this study is a closed questionnaire that has been tested to 30 teenagers outside the research sample.The result of the experimental test of questionnaire X variable was 0,836 and Y was 0,914 with very strong correlation index. The results obtained by the value of correlation coefficient test = rhitung rtabel 0,457 0,294, the value obtained ttabel yaitu 3,37 2,021, the value of coefficient of determination obtained r2 x 100% = 0,457 x 100% = 20,88%, and obtained the value Fhitung Ftabel yaitu 42,21 1,51. Based on the results of this study can be concluded that the research hypothesis that reads: “there is significant and significant influence between parental responsibility to the spiritual growth of adolescents aged 13-16 years in the Desa Lumban Lobu Kecamatan Bonatua Lunasi Kabupaten Toba Samosir is acceptable. Keywords: parental responsibility, to the spiritual growth of teenagers.